Risk factors for diabetes mellitus after acute pancreatitis: a systematic review and meta-analysis - Zahariev, Olga Julia; Bunduc, Stefania; Kovács, Adrienn; Demeter, Dóra; Havelda, Luca; Budai, Bettina Csilla; Veres, Dániel Sándor; Hosszúfalusi, Nóra; Erőss, Bálint Mihály; Teutsch, Brigitta; Juhász, Márk Félix; Hegyi, Péter (Frontiers in Medicine, 2024)
Introduction Within 5 years of having acute pancreatitis (AP), approximately 20% of patients develop diabetes mellitus (DM), which later increases to approximately 40%. Some studies suggest that the prevalence of prediabetes (PD) and/or DM can grow as high as 59% over time. However, information on risk factors is limited. We aimed to identify risk factors for developing PD or DM following AP. Methods We systematically searched three databases up to 4 September 2023 extracting direct, within-study comparisons of risk factors on the rate of new-onset PD and DM in AP patients. When PD and DM event rates could not be separated, we reported results for this composite outcome as PD/DM. Meta-analysis was performed using the random-effects model to calculate pooled odds ratios (OR) with 95% confidence intervals (CI). Results Of the 61 studies identified, 50 were included in the meta-analysis, covering 76,797 participants. The studies reported on 79 risk factors, and meta-analysis was feasible for 34 risk factor and outcome pairs. The odds of developing PD/DM was significantly higher after severe and moderately severe AP (OR: 4.32; CI: 1.76–10.60) than mild AP. Hypertriglyceridemic AP etiology (OR: 3.27; CI: 0.17–63.91) and pancreatic necrosis (OR: 5.53; CI: 1.59–19.21) were associated with a higher risk of developing PD/DM. Alcoholic AP etiology (OR: 1.82; CI: 1.09–3.04), organ failure (OR: 3.19; CI: 0.55–18.64), recurrent AP (OR: 1.89; CI: 0.95–3.77), obesity (OR: 1.85; CI: 1.43–2.38), chronic kidney disease (OR: 2.10; CI: 1.85–2.38), liver cirrhosis (OR: 2.48; CI: 0.18–34.25), and dyslipidemia (OR: 1.82; CI: 0.68–4.84) were associated with a higher risk of developing DM. Discussion Severe and moderately severe AP, alcoholic and hypertriglyceridemic etiologies, pancreatic necrosis, organ failure, recurrent acute pancreatitis and comorbidities of obesity, chronic kidney disease liver disease, and dyslipidemia are associated with a higher risk of developing PD or DM. Systematic review registration: https://www.crd.york.ac.uk/prospero/, identifier CRD42021281983.